Tsunami data assimilation and forecast in the Kii Channel using high-frequency radar: Bathymetry effects on the propagation of measurement errors - Muhammad Irham Sahana; Ryotaro Fuji; Hirofumi Hinata (Ocean Modelling, 2026)

Oceanographic characteristics in the North of Aceh waters - Yudi Haditiar; Muhammad Ikhwan; Saiful Mahdi; Ananda Novita Siregar; Haekal Azief Haridhi; Ichsan Setiawan; Muhammad Nanda; Vicky Prajaputra; Muhammad Irham (Regional Studies in Marine Science, 2024)

Study of the suitability of rock type with the chemical typology of groundwater in the Jeunib basin, Aceh - Muhammad Irham; Muhammad Irpan; Dewi Sartika; Gartika Setiya Nugraha; Dian Budi Dharma (Arabian Journal of Geosciences, 2022)

Coastal Vulnerability of the West Coast of Aceh Besar: A Coastal Morphology Assessment - Muhammad Irham; Ichsan Rusydi; Haekal A. Haridhi; Ichsan Setiawan; Yopi Ilhamsyah; Anwar Deli; Muhammad Rusdi; Annisa Mardiah Siregar (Journal of Marine Science and Engineering, 2021)
The purpose of this study was to determine how vulnerable the west coast of Aceh Besar, Aceh province, Indonesia, is in terms of its coastal morphology. This research was conducted from August to December 2020 and data processing was carried out at the Geographical Information Systems Laboratory, Faculty of Marine Affairs and Fisheries, Syiah Kuala University. The method used was the coastal vulnerability index (CVI) with four geological parameters, namely geomorphological parameters, beach elevation, beach slope and shoreline changes. The results obtained from the CVI method show that 20.60% of the west coast of Aceh Besar, which has a total coastline length of 93.2 km, is in the very high vulnerability category (19.2 km), while 23.18% (21.6 km) is in the high vulnerability category, 8.80% (8.2 km) in the moderate category, 6.44% (6 km) in the low category and 40.99% (38.2 km) in the very low category. Sub-districts classified as having very high vulnerability are Peukanbada (7.94%), Leupung (6.22%), Lhoong (4.94%), and Lhoknga (1.50%). The geomorphology of areas that have very high vulnerability is generally in the form of sandy beaches with a very gentle slope, while, geomorphologically, areas that have very low vulnerability have a high elevation and cliff beaches.